Land Mosaics : The Ecology of Landscapes and Regions - Forman, Richard T. T. (Cambridge : Cambridge University Press, 1995)
Animals, plants, water, wind, materials and people flow at different rates, according to spatial patterns common to almost all landscapes and regions. This up-to-date synthesis explores the ecology of heterogeneous land areas, where natural processes and human activities spatially interact, to produce an ever changing mosaic. The subject has great relevance to today's society, and this book reflects the breadth of its importance; there are many ideas and applications for planning, conservation, design, management, sustainability and policy. Spatial solutions are provided for society's land-use objectives. An appealing book, with a highly-readable text on this major emerging field. Students and professionals alike will be drawn by the attractive and informative illustrations, the conceptual synthesis, the wide international perspective and the range of topics and research covered.
Title from publisher's bibliographic system (viewed on 15 Oct 2018).
Keywords: elektronické knihy; electronic books; Environmental policy; Landscape ecology; Human ecology; Young adult drama, English